SWINE FLU- THE CHANGING SCENARIO AND PREPAREDNESS WITH FORMULATION OF WIN FLU AIR FRESHENER GEL - Garg, Ayush Kumar; Singh, Amit; Vishnoi, Harish; Meena, Gulab Chand; Singh, Chandan; Adlakha, Manoj (International Journal of Ayurveda and Pharma Research, 2017)
Swine flu is an emerging viral infection that is a present global public health problem. There are many thousand cases of swine flu can be seen around the world in the present day. Due to the nature of a respiratory virus, the transmission of this pathogenic virus is airborne transmission. Hence, the rapid spreading and difficulty in control of this infection can be expected. Ayurved believes in Nidan parivarjan and recommends the strengthening of the immunity to prevent disease like swine flu from its attack. There are no any medicines or vaccination are available now a days for prevent from swine flu. Mask is an only available option from avoiding the virus, but sometimes it fails to stop the infection and peoples are unable to wearing mask for all time. So there is a need to develop such a thing which we can carry easily with us and protecting from the infection. Many environment purification techniques (like Homa, Yagya, Dhoopana) have been mentioned in our classical texts. Several scientific studies have validated the clinical efficacy of air freshener against the viral stains. Freshener is a household product that can release the chemicals they contain into the air and inhaled by consumers. The purpose of this research is to determine the ability of herbal essential oil to be formulated as a WIN FLU- air freshener gel with fragrance of citrus oil and binder of peppermint oil. Gel formulation in the study was made from a mixture of herbal essential oil (carom seed, Eucalyptus, Basil, Ginger, Clove), sodium benzoate, peppermint and citrus essential oil in distilled water with a variety of different concentrations of herbal essential oil at 1%, 2% and 3%, then performed an evaluation form hedonic test gel with 30 panelists, evaporation of a liquid test during 4 weeks of storage. The results of this study indicate that the best gel formula is the formula A3 with an herbal essential oil concentration of 3%. Results per cent of total evaporation of liquid air freshener gel formula are respectively 59.12%, 42.32%, 21.22%.